2010
DOI: 10.1111/j.1369-1600.2010.00206.x
|View full text |Cite
|
Sign up to set email alerts
|

Implications for glycine receptors and astrocytes in ethanol-induced elevation of dopamine levels in the nucleus accumbens

Abstract: Elevated dopamine levels are believed to contribute to the rewarding sensation of ethanol (EtOH), and previous research has shown that strychnine-sensitive glycine receptors in the nucleus accumbens (nAc) are involved in regulating dopamine release and in mediating the reinforcing effects of EtOH. Furthermore, the osmoregulator taurine, which is released from astrocytes treated with EtOH, can act as an endogenous ligand for the glycine receptor, and increase extracellular dopamine levels. The aim of this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 54 publications
4
42
0
Order By: Relevance
“…This finding was also confirmed in slices treated with PMBA, which has been reported not to interact with α 7 nicotinic acetylcholine, NMDA, or GABA A receptors when used at concentrations below 100 μM (Saitoh et al, 1994;Renna et al, 2007). The glycine receptor can be activated by glycine, taurine, and β-alanine, and microdialysate sampling from the nAc has shown that all three agonists are present at measurable levels during baseline conditions (Lidö et al, 2009;Adermark et al, 2011). This, in connection with the present data, indicates that the glycine receptor is most likely endogenously activated during baseline conditions.…”
Section: Glycinergic Modulation Of Excitatory Input and Extracellularsupporting
confidence: 57%
“…This finding was also confirmed in slices treated with PMBA, which has been reported not to interact with α 7 nicotinic acetylcholine, NMDA, or GABA A receptors when used at concentrations below 100 μM (Saitoh et al, 1994;Renna et al, 2007). The glycine receptor can be activated by glycine, taurine, and β-alanine, and microdialysate sampling from the nAc has shown that all three agonists are present at measurable levels during baseline conditions (Lidö et al, 2009;Adermark et al, 2011). This, in connection with the present data, indicates that the glycine receptor is most likely endogenously activated during baseline conditions.…”
Section: Glycinergic Modulation Of Excitatory Input and Extracellularsupporting
confidence: 57%
“…In particular, taurine is present in high concentrations in brain and acts as a partial agonist at GlyR receptors (Wu and Prentice, 2010). Microdialysis studies reveal that EtOH applied systemically or locally induces a rapid increase in extracellular taurine levels in the nucleus accumbens (Adermark et al, 2011;Smith et al, 2004) with much less effect in dorsal striatum (Smith et al, 2004) suggesting brain regional differences in EtOH-taurine interactions. The mechanisms underlying this effect are not completely known but may involve an EtOH-induced increase in astrocyte volume that triggers a release of taurine in order to maintain osmotic pressure in these cells.…”
Section: Etoh Decreases Intrinsic Excitability Of Ofc Neuronsmentioning
confidence: 99%
“…The mechanisms underlying this effect are not completely known but may involve an EtOH-induced increase in astrocyte volume that triggers a release of taurine in order to maintain osmotic pressure in these cells. For example, (Adermark et al, 2011) showed that EtOH caused swelling in 15-17% of cultured rat astrocytes and that this effect was similar for both 25 and 50 mM EtOH. These concentrations are within the range of those found in the present study (11-66 mM) to reduce spike firing of lOFC neurons.…”
Section: Etoh Decreases Intrinsic Excitability Of Ofc Neuronsmentioning
confidence: 99%
“…Taurine has previously been shown to increase accumbal dopamine levels, and appears to be a key component in ethanol induced dopamine release [76][77][78]. Considering the role of dopamine in mediating the rewarding sensation of drugs of abuse, it is thus possible that astrocytes are indirectly involved in ethanol-induced reinforcement [65, 79,80]. Rapid swelling and regulatory volume decrease is facilitated by astrocytic water channels built up by the protein aquaporin-4 [81,82], and reduced aquaporin-4 expression has in fact also been linked to excessive alcohol consumption [83].…”
Section: Astrocytic Cell Swellingmentioning
confidence: 99%
“…Especially, glycine receptors could be important regulators of ethanol induced reinforcement as antagonists targeting glycine receptors both blocks the dopamine-elevating property of ethanol in vivo, as well as prevents ethanol-induced changes in striatal neurotransmission ex vivo [79,111,112]. In addition, inhibition of the glycine transporter GlyT1 persistently reduces ethanol intake and relapse-like alcohol drinking in rats [113][114][115][116], and might thus be a pharmacological target for the treatment of alcohol abuse disorders.…”
Section: Astrocytic Amino Acid Transporters and Ethanolmentioning
confidence: 99%